Simplify: (5x - 10)2

(5x - 10)^2 = 25x^2 - 100x + 100

Expert answered|andrewpallarca|Points 20326|

Question

Asked 3/20/2013 12:38:42 AM

Updated 3/7/2016 9:27:53 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by jeifunk [3/7/2016 9:27:51 AM]

s

Rating

There are no new answers.

Simplify: (x - 4)2 **Weegy:** b(a + b) - a(a - b) is equal to n^2-a^2+2ab or -a^2+2ab+b^2. SOLUTION: b(a + b) - a(a - b) ab+b^2-a^2+ab b^2-a^2+ab+ab n^2-a^2+2ab or -a^2+2ab+b^2 **User:** Simplify: (x - 4)^2. (A)x^2 - 16 (B) x^2 - 8 (C) x^2 - 8x + 16 (D) x2 - 16x + 8^ (More)

Question

Not Answered

Updated 7/2/2014 8:40:19 PM

1 Answer/Comment

(x - 4)^2 = (x - 4)(x - 4) = x^2 - 4x - 4x + 16 = x^2 - 8x + 16

Added 7/2/2014 8:40:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/4/2014 4:57:36 PM]

Which description best fits the number one? (A) prime (B) composite (C) neither

Question

Updated 1/4/2016 4:22:09 AM

1 Answer/Comment

Simplify: (5x - 10)2 **Weegy:**
(5x - 10)^2
= (5x - 10)(5x - 10)
= 25x^2 - 50x - 50x + 100
= 25x^2 - 100x + 100
**User:** Multiply: (m + 7) (m - 7). (More)

Question

Not Answered

Updated 6/16/2014 12:03:19 PM

1 Answer/Comment

(m + 7) (m - 7)

= m^2 - 7m + 7m - 49

= m^2 - 49

= m^2 - 7m + 7m - 49

= m^2 - 49

Added 6/16/2014 12:03:19 PM

This answer has been confirmed as correct and helpful.

Multiply: (m + 7) (m - 7). **Weegy:** (m + 7) (m - 7) = m^2 - 49 (More)

Question

Expert Answered

Updated 3/25/2014 1:54:18 PM

0 Answers/Comments

Multiply: (8a + 5b) (8a - 5b). **Weegy:** (8a + 5b) (8a - 5b) = 64a^2 - 25b^2 (More)

Question

Expert Answered

Updated 3/7/2016 9:28:17 AM

0 Answers/Comments

31,876,817

questions answered

There are no comments.